Pelatihan Keamanan Data Pada Penggunaan Microsoft Office Bagi Guru di SDIT Mutiara Bekasi - Nurfiyah, Nurfiyah; Salkiawati, Ratna; Lubis, Hendarman (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Information Technology Security is increasingly advanced, not only in the world of the manufacturing industrybut also penetrates the world of education. This forces educators to be able to develop their abilities to know howto secure data in Ms.Office. Therefore, as a manifestation of Bhayangkara Jakarta Raya University's commitmentto carrying out the Tri Dharma of Higher Education in community service, the Informatics Study Program carriedout activities with the theme